PEMBELAJARAN MULTIMEDIA DAN TKJ DI SMK NEGERI 6 SUKOHARJO - Rendiko Raditya Wibowo; Tasya Tanjung Wulan; Hanifah Nursanti (Buletin Literasi Budaya Sekolah, 2022)
Students as an asset for the nation, therefore it is necessary to develop properly. The PLP 1 activity itself takes place at the school premises at SMK N 6 Surakarta where there are several processes of observing and also the learning process which will later be carried out in a hybrid or online manner due to the current Covid -19 pandemic situation which has developed again.[MU1]  The application of various learning models is considered capable of increasing the enthusiasm and activeness of students in the learning process. Research will use descriptive qualitative types, observations, and interviews. The obstacle for the students was that during the pandemic students really did not have an idea of the subject matter, and when students entered school they did not have sufficient subject matter. then for the targets that have been achieved which have been generated from the vision and mission of SMK N 6 Sukoharjo, they are classified as meeting the achievement targets and we will continue to develop them in the future for alumni graduates so that they are even better and also ready to work wherever they are placed. Based on the results of the implementation and discussion it can be concluded that in each cycle there is an increase. Where in each of these cycles with different quiz paper questions. With this it can be said that the increase in student learning outcomes in each cycle at meeting I and meeting II has increased.